Mekanisme Koreksi Fiskal Laporan Keuangan atas Pajak Penghasilan pada PT ABC - Eka Tresia Dia Agustin (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Fiscal correction in its implementation, there is a difference in treatment between financial accounting standards and tax provisions so that the company's commercial profit cannot be directly used as a basis for calculating Corporate Income Tax (PPh), fiscal reconciliation is needed through a fiscal correction process to adjust commercial profit to fiscal profit. The method used is a descriptive method with a qualitative and quantitative approach. Data collection techniques are carried out through observation, documentation, interviews, and literature studies. The results of the discussion show that PT ABC has several accounts that require fiscal adjustments, including inventory depreciation, educational reserves, transportation and fuel, reserves for doubtful accounts, PPAP formation, donations, savings interest, deposit interest, giro service interest, use of educational reserves, PPAP recovery, use of employee benefit reserves, and principal loss. PT ABC is in an overpayment position because the amount of tax credits that have been paid is greater than the actual tax liability.
Finalisasi 28 Juli 2026 Rudi H
Keywords: fiscal correction; corporate income tax; fiscal reconciliation